Contemporary Management of Cardiogenic Shock: A RAND Appropriateness Panel Approach. (22nd November 2021) - Proudfoot, Alastair G.; Kalakoutas, Antonis; Meade, Susanna; Griffiths, Mark J.D.; Basir, Mir; Burzotta, Francesco; Chih, Sharon; Fan, Eddy; Haft, Jonathan; Ibrahim, Nasrien; Kruit, Natalie; Lim, Hoong Sern; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Current practice in cardiogenic shock is guided by expert opinion in guidelines and scientific statements from professional societies with limited high quality randomized trial data to inform optimal patient management. An international panel conducted a modified Delphi process with the intent of identifying aspects of cardiogenic shock care where there was uncertainty regarding optimal patient management. Methods: An 18-person multidisciplinary panel comprising international experts was convened. A modified RAND/University of California Los Angeles appropriateness methodology was used. A survey comprising 70 statements was completed. Participants anonymously rated the appropriateness of each statement on a scale of 1 to 9: 1 to 3 inappropriate, 4 to 6 uncertain, and 7 to 9 appropriate. A summary of the results was discussed as a group, and the survey was iterated and completed again before final analysis. Results: There was broad alignment with current international guidelines and consensus statements. Overall, 44 statements were rated as appropriate, 19 as uncertain, and 7 as inappropriate. There was no disagreement with a disagreement index <1 for all statements. Routine fluid administration was deemed to be inappropriate. Areas of uncertainty focused panel on pre-PCI interventions, the use of right heart catheterization to guide management, routine use of left ventricular unloading strategies, and markers of futility when considering escalation to mechanical circulatory support. Conclusions: While there was broad alignment with current guidance, an expert panel found several aspects of care where there was clinical equipoise, further highlighting the need for randomized controlled trials to better guide patient management and decision making in cardiogenic shock.